“I AM MENTALLY HEALTHY, SO I CAN CHOOSE WELL.” QUARTER-LIFE CRISIS AND POSITIVE MENTAL HEALTH IN STUDENTS - Herdian Herdian; Dzikria Afifah Primala Wijaya (Tạp chí Khoa học Đại học Đà Lạt)
The transition from adolescence to adulthood is marked by psychosocial and other psychological changes. Quarter-life crisis is a symptom that appears during the transition period. We examined how quarter-life crisis impacts mental health using a convenience sampling technique. A total of 459 students, 18 to 25 years old, filled out questionnaires distributed online. The data measurement tool used quarter-life crisis and positive mental health scales adjusted into Indonesian form. The results show a significant negative correlation (R = -0.437; p <  .001) between quarter-life crisis and positive mental health in students. The regression analysis shows an impact of quarter-life crisis on positive mental health of 19%, which is relatively small. The implications of our research results are discussed.